2015
DOI: 10.1021/jacs.5b01121
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of E–H (E = N, O) Bond Activation by a Germanium Corrole Complex: A Combined Experimental and Computational Study

Abstract: (TPFC)Ge(TEMPO) (1, TPFC = tris(pentafluorophenyl)corrole, TEMPO(•) = (2,2,6,6-tetramethylpiperidin-1-yl)oxyl) shows high reactivity toward E-H (E = N, O) bond cleavage in R1R2NH (R1R2 = HH, (n)PrH, (i)Pr2, Et2, PhH) and ROH (R = H, CH3) under visible light irradiation. Electron paramagnetic resonance (EPR) analyses together with the density functional theory (DFT) calculations reveal the E-H bond activation by [(TPFC)Ge](0)(2)/TEMPO(•) radical pair, generated by photocleavage of the labile Ge-O bond in compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…In contrast to the [(TPFC)­Ge] + cation, the vacant orbitals on these cationic centers were the two pure p orbitals (schematic representation of 1-coordinate E­(II) cation in Figure c). , This work presents a rare example of group 14 cations with vacant sp-hybridized orbitals illustrating its distinctive reactivity. Similarly, our previous studies , showed that the unpaired electron in the [(TPFC)­Ge] 0 radical was mainly localized in a sp-hybridized orbital on the germanium center rather than in a pure p orbital as is typical of the traditional heavier group 14 radicals. , …”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…In contrast to the [(TPFC)­Ge] + cation, the vacant orbitals on these cationic centers were the two pure p orbitals (schematic representation of 1-coordinate E­(II) cation in Figure c). , This work presents a rare example of group 14 cations with vacant sp-hybridized orbitals illustrating its distinctive reactivity. Similarly, our previous studies , showed that the unpaired electron in the [(TPFC)­Ge] 0 radical was mainly localized in a sp-hybridized orbital on the germanium center rather than in a pure p orbital as is typical of the traditional heavier group 14 radicals. , …”
Section: Resultssupporting
confidence: 62%
“…4,27 This work presents a rare example of group 14 cations with vacant sphybridized orbitals illustrating its distinctive reactivity. Similarly, our previous studies 36,62 showed that the unpaired electron in the [(TPFC)Ge] 0 radical was mainly localized in a sphybridized orbital on the germanium center rather than in a pure p orbital as is typical of the traditional heavier group 14 radicals. 63,64 ■ CONCLUSIONS A square planar, tetra-coordinated Ge(IV) cation, [(TPFC)-Ge] + , was synthesized through the reaction of (TPFC)Ge−H with [Ph 3 C] + [B(C 6 F 5 ) 4 ] − .…”
Section: ■ Introductionsupporting
confidence: 63%
“…Their direct application to estimating reaction and activation free energies for processes even in highly dilute solutions, not to mention the concentrated multicomponent reactive systems commonly encountered in practical catalysis, should be done with certain care. 136,240,241…”
Section: Competition Between Methods and Model Accuracies In Computatimentioning
confidence: 99%
“…In solution this can lead to errors in the calculated entropy of up to 60 kJ/mol. 90 In solution, reactions only take place when reactants approach each other in the same solvent cage, thus, the majority of translational and rotational degrees of freedom is already suppressed due to interactions with solvent molecules. Therefore, the calculation of reactant complexes according to a (hypothetical) situation of not or only weakly interacting reactants is advisable.…”
Section: Computational Detailsmentioning
confidence: 99%